The Current Situation and Development Trend of China’s Education Policy Under the Background of the COVID-19 Pandemic - Байшань, Гулицзи (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
In recent years, with the development of global information technology, the field of education has gradually moved toward modernization and began to diversify. The outbreak of COVID-19 in 2020 has brought an unprecedented impact on education around the world, changing the traditional education model, promoting the vigorous development of online education, and giving birth to a new form of education. In this context, how to adapt to the changes of The Times, how to ensure the quality of education, how to ensure the steady development of education, is one of the most concerning issues in the world at present. This paper first introduces the four-phased education policies adopted by China since the outbreak of COVID-19, analyzes the challenges faced by China’s education, and describes how China’s education can seize the opportunities to meet the challenges, form a new model of education governance, promote online education, and fundamentally ensure the orderly, convenient, and efficient operation of all educational work. Finally, the future development trend of Education informatization in China is discussed, which leads to education modernization, promotes education fairness, and creates a good education environment.